Assessing prefrontal cortex activity in Graves’ disease: a functional near-infrared spectroscopy study - Skau, Simon; Holmberg, Mats; Johansson, Birgitta; Bunketorp Käll, Lina; Malmgren, Helge; Kuhn, Hans-Georg; Filipsson Nyström, Helena (Frontiers in Human Neuroscience, 2025)
IntroductionGraves’ disease (GD) is associated with cognitive, emotional, and fatigue difficulties. Objective measures of cognitive dysfunction have yielded mixed results. The aim of this study was to investigated whether premenopausal female patients with first-time hyperthyroid GD (mean age 34 years) exhibit cognitive fatigability and altered functional activity in the prefrontal cortex (PFC) using functional near-infrared spectroscopy (fNIRS) during an exhausting cognitive task.MethodsUsing the Animal Stroop test, we compared patients with GD (N = 28) and healthy controls (N = 28) before and after a 30-min cognitively exhausting reading comprehension task.ResultsBoth groups showed improvements in Stroop task performance after the reading task (p < 0.001, ηp2 = 0.389), and no group differences were observed in cognitive performance. Increased activation in the left dorsolateral prefrontal cortex post-test was found for controls but not for patients with GD. Exploratory analyses showed higher increases in oxy-hemoglobin levels post-test in the PFC of controls compared to patients with GD, indicating reduced PFC involvement in patients with GD.DiscussionIn conclusion, we were not able to show any change in the functional activity of the PFC after prolonged mental activity in this set-up using fNIRS of hyperthyroid GD patients. Further studies are needed to understand the mechanism behind self-reported fatigue in GD.